Virulence traits and antibiotic resistance among enterococci isolated from dogs with periodontal disease. (June 2016) - Oliveira, Manuela; Tavares, Marta; Gomes, Diana; Touret, Tiago; São Braz, Berta; Tavares, Luís; Semedo-Lemsaddek, Teresa
Highlights: The presence of enterococci in the oral mucosa was dogs with periodontal disease (PD) was investigated. Pathogenicity potential of the PD-enterococci was evaluated. PD-isolates harbor virulence traits, form biofilm and present antibioressistances. Owners must be alerted of this hazard and informed on preventive actions. Abstract: Periodontal disease – PD – is one of the most widespread diseases in dogs, but the role of this odontogenic infection in the dissemination of pathogenic bacteria present in the oral mucosa to other animals or pet owners is understudied. Trying to unveil the putative pathogenicity of enterococci present in the gums of dogs diagnosed with PD, thirty-two animals were investigated during routine visits to a private veterinary clinic. Seventy-one enterococci were recovered and characterized regarding species, genomic variability, virulence traits, antimicrobial resistance and biofilm-forming ability. Isolates were mainly identified as E nterococcus faecalis, with the large majority (95%) being able to produce biofilm. Regarding antibiotic resistance, all dog-enterococci were susceptible to ampicillin, amoxicillin/clavulanate, gentamicin-120, imipenem and vancomycin; while distinct levels of resistance were observed for chloramphenicol (10%), erythromycin (20%), streptomycin-300 (35%) and tetracycline (95%). For virulence traits incidence levels of 35% were observed for β-hemolysis and 25% for cylA, 25% for gelatinase and 35% for gelE; 85% harbor efaAfs and ebpABC ; while ace, agg and esp are present respectively in 50, 30 and 10% of the dog-enterococci; efaAfm and acm were detected in all the E nterococcus faecium. Overall, the widespread prevalence of PD in dogs, associated with the close contact between companion animals, other animals and humans, may act as source for the dissemination of opportunistic pathogenic bacteria. Hence, aforementioned data on virulence and resistance features, emphasizes the need for active surveillance measures, such as the diagnose of PD in companion animals during routine visits to the veterinary clinic.